FROM BIOMIMICRY TO ARCHITECTURE: THE FUTURE OF RESPONSIVE SHADING - Oliveira, M.J. (Advanced Functional Materials & Biomaterials & Biodevices, 2024)
Architecture has evolved with industrial and material advancements, climatic constraints, new technological capacities, societal changes, and cultural premises. Biomimetic processes have proven effective in addressing various problems, including diseases and material challenges. While we possess the knowledge to solve current challenges, building interdisciplinary bridges remains essential. One major challenge in transdisciplinary teams is the lexicon. Biomimetics, already sharing terminology with fields like engineering and medicine, could enhance architectural responsiveness and interaction if integrated into architecture schools and practices. The aim is to develop a problem-based methodology, the Bioshading System Design Methodology (BSDM), using natural events as models to create performative and design solutions for responsive shading systems. BSDM operates through a circular relationship among three domains: Architecture, Nature, and Artifact. Each domain represents a stage in the design process. The “Architecture” domain involves defining the architectural challenge; the “Nature” domain involves abstracting natural elements to create the Biomeme, which supports the shading system design concept; and the “Artifact” domain involves emulating this concept to develop the architectural design solution. While the final prototype is crucial, the richness of information and experience gained during the BSDM process is key to its success. BSDM users will be capable of observing, analyzing, reconfiguring, and improving their shading solutions in ways that would not have been possible without this methodology. BSDM integrates Architecture, Biology, and Digital Tools to create efficient, environmentally responsive shading systems. The most significant contribution is the dissolution of disciplinary boundaries, fostering robust connections among these fields. This transdisciplinary approach enables the creation of a common lexicon and the development of the Biomeme—an inspirational, human-made biological concept that provides the fundamental characteristics for the shading system.